Infection with gastrointestinal nematodes in lambs in different integrated crop-livestock systems (ICL) - Almeida, Fabiana A. [UNESP]; Piza, Marina L.S.T. [UNESP]; Bassetto, César C. [UNESP]; Starling, Renan Z.C. [UNESP]; Albuquerque, Ana Cláudia A. [UNESP]; Protes, Verena M. [UNESP]; Pariz, Cristiano M. [UNESP]; Castilhos, André M. [UNESP]; Costa, Ciniro [UNESP]; Amarante, Alessandro F.T. [UNESP] (Elsevier, 2018)
Lamb performance was evaluated in four integrated crop-livestock (ICL) systems. The ICL areas were previously planted with maize and marandu palisade grass in December 2013. ICL systems 1 and 2 were also seeded with pigeon pea. After harvesting in April 2014, black oats were sown in rows (ICL 1 and 3) or by broadcast seeding (ICL 2 and 4). Each ICL area was divided into 12 paddocks of 225 m2 to be grazed by young sheep from July 23 to September 30, 2014. To determine if the pasture remained contaminated by free-living stages of sheep gastrointestinal nematodes (GIN) after approximately ten months without animals in the area, 12 worm-free “tracer” lambs (n = 3/ ICL system) grazed each ICL pasture for 14 consecutive days in July 2015 and were later housed in pens, where they remained for another 14 days. The tracer lambs acquired no worm infections, demonstrating that the area was cleared after 300 days without animals. To evaluate GIN infection and uncastrated male lamb performance, we used 60 (n = 15/ system) Poll Dorset x Corriedale (crossbred) sheep with mean body weights of 24.4 ± 3.4 kg from July to September 2015 and 48 (n = 12/ system) Texel x Corriedale sheep with body weights of 26.4 ± 3.5 kg from June to September 2016. Lambs were allocated to the following groups: Group 1 rotated on the 12 ICL1 paddocks; Group 2 rotated on the 12 ICL2 paddocks; Group 3 rotated on the 12 ICL3 paddocks; and Group 4 rotated on the 12 ICL4 paddocks. Each paddock was grazed by sheep twice for three days, with a 33-day interval between grazing. At the end of the day the lambs were supplemented with concentrate plus silage. Groups 1 and 2 received mixed silage made of maize, marandu palisade grass and pigeon pea and groups 3 and 4 received mixed silage made of maize and marandu palisade grass. Faecal and blood samples were taken from all the animals every two weeks, and body weight was recorded on the same occasion. Nematode faecal egg counts (FEC), packed cell volume and total plasma protein means did not differ (P > 0.05) between the four lamb groups. In 2015, throughout the experimental period, the FEC decreased in all animals, with 6733 and 1407 eggs per gram (EPG) on average at the beginning and end of the trial, respectively. At the beginning of the trial in 2016, the animals had mild GIN infections (1077 EPG on average), and the individual faecal egg counts did not exceed 10,000 EPG during the trial. In decreasing order, Haemonchus spp., Trichostrongylus spp. and Cooperia spp. third stage larvae were found in the faecal cultures in both years. The performance of lambs were similar in the four ICL systems (P > 0.05), in the first and second years, the daily weight gains were 0.192 ± 0.05 kg and 0.221 ± 0.06 kg, respectively. In conclusion, a period of withdrawal of contaminated sheep results in plots free of infective larvae. The use of clean pastures during the dry season, in the different ICL systems, associated with a good nutrition plan, resulted in progressively declining degrees of GIN infections and satisfactory daily weight gain of young sheep.
Keywords: Control; Haemonchus; nematodes; Sustainability; Trichostrongylus